Assessment of knowledge about seasonal influenza and practice of influenza vaccination in a sample of Iraqi diabetic patients - Ali L. Jasim (Pharmacia)
Administering influenza vaccines can prevent seasonal influenza and prevent or reduce the severity of influenza-related serious complications in diabetic patients. We aimed to assess the knowledge about seasonal influenza and its vaccines and the practice of influenza vaccination in a sample of Iraqi diabetic patients.A cross-sectional study was conducted on adult diabetic Iraqi patients. The data was collected by a well-trained community pharmacist using a paper-based, structured questionnaire. Most participants understood influenza well and answered the knowledge part of the questionnaire effectively. Over 50% of the participants had heard or knew about the influenza vaccine, and 43.2% agreed that seasonal influenza is a mild condition and does not require the administration of any vaccine. The vast majority of participants (75.7%) agreed with the statement that they would take a vaccine if it were a good vaccine for preventing influenza. Less than one-third of participants (32.4%) previously received the influenza vaccine. The recommendation of a friend or family member, followed by physician instruction, significantly influenced most vaccine participants (47.2% and 44.4%, respectively). On the other hand, the most frequent cause of avoiding vaccination was the perception of seasonal influenza as a mild illness (57.3%). In conclusion, most participants had good knowledge about seasonal influenza and its vaccines. The highest percentage of participants, less than that in the knowledge part, revealed positive attitudes towards seasonal influenza and its vaccines. Unfortunately, about two-thirds of participants had not taken influenza vaccines previously because most considered seasonal influenza a mild illness.